Inflation and Income Inequality : Is Food Inflation Different? - Walsh, James (IMF Working Papers; Working Paper ;, 2012)
There is an extensive literature noting that high inflation can add to income inequality, and a parallel literature assessing the effect of rising food prices on the poor. This paper attempts to combine these strands by dividing inflation into food and nonfood inflation and assessing whether food inflation affects income inequality differently from nonfood inflation. In an international sample and a sample of Chinese provinces, nonfood inflation exacerbates income inequality while the role of food inflation is more mixed. In a sample of Indian states broken down into urban and rural areas, we find that nonfood inflation adds to income inequality in both areas, while food inflation has a neutral to positive effect on income inequality in rural areas, providing support for the theory that rural wages may respond elastically to food prices.